STUDENTS’ LANGUAGE LEARNING STYLE PREFERENCES AT ENGLISH LITERATURE STUDY PROGRAM - Setya Ariani; Nita Maya Valiantien; Noor Rachmawaty (CaLLs: Journal of Culture, Arts, Literature, and Linguistics)
Learning style is one of the factors contributing to students’ success on second or foreign language learning. This present research attempted to identify various learning styles used in learning English by administering Perceptual Learning Style Preference Questionnaire ( PLSPQ ) for 121 EFL students at English literature study program. The result of descriptive analysis showed that the overall students’ preferred learning style was found to be auditory (M= 37.5, SD = 4.48). Based on gender differences, a majority of male students were auditory students ( M = 38.6, SD = 4.27)  and most of the female students were observed to have tendency to be in the category of kinaesthetic students (M = 3.69, SD = .49). The individual learning style became the least frequent style used by the students ( M = 35.2, SD = 7.53). The findings contribute to the improvement of teaching practice quality. Educators are recommended to employ various teaching styles and design variety of activities that enable students to activate their own learning styles more effectively.